Carbon nanotube chirality enrichment through chirality‐selective precipitation. Issue 12 (10th November 2016) - Setaro, Antonio; Bluemmel, Pascal; Witt, Marcus Ulf; Narula, Rohit; Reich, Stephanie
Abstract : The interaction with surfactants changes from one carbon nanotube species to the other. We used this to replace non‐ionic surfactants by ionic ones. By fine‐tuning the replacement conditions, we covered some specific nanotubes with non‐ionic surfactants and the others with ionic ones. Addition of salt triggers precipitation of the species suspended by the ionic surfactant; this effectively leads to chiral selective enrichment of a carbon nanotube suspension. We hence produce an (8, 4)‐enriched suspension by replacing a polyglycerol‐based custom amphiphile with the commercial SDBS and salting with NaCl. Relative sample composition, before and after the salting‐out procedure.